Sequencing impact and prognostic factors in metastatic castration-resistant prostate cancer patients treated with cabazitaxel: A systematic review and meta-analysis - Yanagisawa, Takafumi; Kawada, Tatsushi; Rajwa, Pawel; Mostafaei, Hadi; Motlagh, Reza Sari; Quhal, Fahad; Laukhtina, Ekaterina; König, Frederik; Pallauf, Maximilian; Pradere, Benjamin; Karakiewicz, Pierre I; Nyirady, Peter; et al. (Urologic oncology, 2023)
BACKGROUND: Cabazitaxel is an effective treatment of post-docetaxel metastatic castration-resistant prostate cancer (mCRPC). We aimed to assess the sequencing impact and identify prognostic factors of oncologic outcomes in mCRPC patients treated with cabazitaxel. METHODS: PUBMED, Web of Science, and Scopus databases were searched for articles published before January 2022 according to the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses) statement. Studies were deemed eligible if they investigated pretreatment clinical or hematological prognostic factors of overall survival (OS) in mCRPC patients with progression after docetaxel treated with available treatments including cabazitaxel. RESULTS: Overall, 22 studies were eligible for the meta-analysis. In mCRPC patients treated with docetaxel, subsequent treatment with cabazitaxel was associated with better OS compared to that without cabazitaxel (pooled hazard ratio [HR]: 0.70, 95% confidence interval [CI]: 0.56-0.89). Among the patients treated with cabazitaxel, several pretreatment clinical features and hematologic biomarkers were associated with worse OS as follows: poor performance status (PS) (pooled HR: 1.92, 95% CI: 1.33-2.77), presence of visceral metastasis (pooled HR: 2.13, 95% CI: 1.62-2.81), symptomatic disease (pooled HR: 1.47, 95% CI: 1.25-1.73), high PSA (pooled HR: 1.76, 95% CI: 1.27-2.44), high alkaline phosphatase (ALP) (pooled HR: 1.45, 95% CI: 1.28-1.65), high lactate dehydrogenase (LDH) (pooled HR: 1.54, 95% CI: 1.00-2.38), high c-reactive protein (CRP) (pooled HR: 4.40, 95% CI: 1.52-12.72), low albumin (pooled HR:1.09, 95% CI: 1.05-1.12) and low hemoglobin (pooled HR:1.55, 95% CI: 1.20-1.99). CONCLUSIONS: Sequential therapy with cabazitaxel significantly improves OS in post-docetaxel mCRPC patients. In mCRPC patients treated with cabazitaxel, patients with poor PS, visceral metastasis, and symptomatic disease were associated with worse OS. Further, pretreatment high PSA, ALP, LDH or CRP as well as low hemoglobin or albumin, were blood-based prognostic factors for OS. These findings might help guide the clinical decision-making for the use of cabazitaxel and prognostication of its OS benefit.
Keywords: Cabazitaxel; Metastatic castration-resistant prostate cancer; Prognosis; Prostatic Neoplasms, Castration-Resistant; výsledek terapie; Docetaxel; mužské pohlaví; nádory prostaty rezistentní na kastraci; Hemoglobins; prostatický specifický antigen; Prognostic factor; docetaxel; Prostate-Specific Antigen; prognóza; Humans; hemoglobiny; Treatment Outcome; lidé; Male